A Systematic Review of Instructional Pedagogies for Teaching Computer Education Among Secondary School Learners in Uganda - Pison Asiimwe; Justine Momanyi Omare; Frank Murangira (Scientia Publica Media, 2026)
Computer Education has become part of modern curricula because of its impact on the development of digital literacy, problem-solving skills, and innovation. Curriculum reforms such as the Competency-Based Curriculum in Uganda have emphasized these competencies through learner-centered methods. However, successful implementation is still limited by the infrastructural factors, the traditional pedagogical methodology, and the lack of proper teacher preparation. The purpose of the study was to find out the most common pedagogical strategies in computer education worldwide, assess their efficiency, and discuss their applicability in education. A systematic literature review was conducted by using PRISMA 2020. ERIC, Scopus, JSTOR, ProQuest, Springer, Sage, Wiley, and Taylor and Francis were used to select 23 peer-reviewed publications published between 2010 and 2025. Constructivist theory, competency-based education, and critical thinking provided the basis of the review. The research involved a content analysis approach, which synthesized evidence on the strategies used in pedagogy, research designs, and learning outcomes. The results show that learner-centered pedagogies, specifically problem-based learning, project-based learning, computational thinking, flipped instruction, and collaborative learning, are most commonly applied and show a significant benefit in terms of increasing the engagement of learners, their critical thinking skills, their problem-solving capabilities, and their computational competence. These strategies are highly aligned with the main competencies highlighted in the competency-based curriculum. Nonetheless, they are hindered by contextual problems, such as the lack of ICT infrastructure, access to technological resources, and a lack of teacher training. The paper concludes that although globally accepted pedagogical strategies are very applicable to competency-based education structures, they require contextualization in order to be effectively implemented. Initiatives should be focused on enhancing teacher capacity, ICT infrastructure, and endorsing context-sensitive instructional practices to be implemented effectively in education environments characterized by resource constraints.